Agonist-induced conformational changes in the G-protein-coupling domain of the β(2) adrenergic receptor - Ghanouni, Pejman (The National Academy of Sciences, 2001)
The majority of extracellular physiologic signaling molecules act by stimulating GTP-binding protein (G-protein)-coupled receptors (GPCRs). To monitor directly the formation of the active state of a prototypical GPCR, we devised a method to site specifically attach fluorescein to an endogenous cysteine (Cys-265) at the cytoplasmic end of transmembrane 6 (TM6) of the β(2) adrenergic receptor (β(2)AR), adjacent to the G-protein-coupling domain. We demonstrate that this tag reports agonist-induced conformational changes in the receptor, with agonists causing a decline in the fluorescence intensity of fluorescein-β(2)AR that is proportional to the biological efficacy of the agonist. We also find that agonists alter the interaction between the fluorescein at Cys-265 and fluorescence-quenching reagents localized to different molecular environments of the receptor. These observations are consistent with a rotation and/or tilting of TM6 on agonist activation. Our studies, when compared with studies of activation in rhodopsin, indicate a general mechanism for GPCR activation; however, a notable difference is the relatively slow kinetics of the conformational changes in the β(2)AR, which may reflect the different energetics of activation by diffusible ligands.